Cambridge primary Mathematics skills builder 2 - Moseley, Cherri; Rees, Janet (New York : Cambridge, 2016)
Cambridge Primary Mathematics is a flexible and engaging course written specifically for Cambridge Primary Mathematics Curriculum Stages 1 to 6. The course offers a discussion-led approach with problem-solving integrated throughout. The language is pitched to ESL learners with illustrations to support visual understanding. Skills Builders provide consolidation activities for children who need extra learning opportunities to meet the standard for success. A full range of activities is provided to help raise a child's mathematical understanding and performance to match their peers, with teacher/parental guidance on key mathematical methods and concepts before each exercise.
Keywords: Mathematics